2023
DOI: 10.1080/07853890.2023.2265298
|View full text |Cite
|
Sign up to set email alerts
|

Approach to COVID-19 in older adults and indications for improving the outcomes

Claudio Tana,
Livia Moffa,
Katia Falasca
et al.

Abstract: Background: COVID-19 continues to present challenges in the care of older adults with frailty and/or comorbidities and very old patients, who can be hospitalized with severe COVID-19 despite full vaccination. Frailty is a heterogeneous syndrome characterized by an increased aging-related vulnerability due to a reduced physiological reserve and function of systemic organs, and is associated with an impairment of activities of daily living. Frail older adults remain at elevated risk of mortality from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…The widespread vaccination against SARS-CoV-2 has radically improved the outcome of patients with COVID-19 and has been associated with a significant overall reduction in mortality. The majority of side effects are mild and transient, therefore periodic vaccination against the SARS-CoV-2 virus is strongly recommended, especially in some at-risk categories of unfavorable outcomes such as immunocompromised patients and older adults [ 52 ].…”
Section: Environmental and Occupational Issues Based On The Example O...mentioning
confidence: 99%
“…The widespread vaccination against SARS-CoV-2 has radically improved the outcome of patients with COVID-19 and has been associated with a significant overall reduction in mortality. The majority of side effects are mild and transient, therefore periodic vaccination against the SARS-CoV-2 virus is strongly recommended, especially in some at-risk categories of unfavorable outcomes such as immunocompromised patients and older adults [ 52 ].…”
Section: Environmental and Occupational Issues Based On The Example O...mentioning
confidence: 99%
“…The long COVID syndrome is a complex condition affecting >20% of subjects who survived moderate and severe forms of COVID-19, especially in the earlier pandemic waves [ 143 ]. This syndrome leads to particularly relevant consequences in older individuals, increasing the burden of frailty and sarcopenia [ 144 , 145 ], and ultimately causing disability and loss of independence [ 146 , 147 ].…”
Section: Diaphragm Ultrasound In Specific Clinical Situations or Dise...mentioning
confidence: 99%
“…After the 2019 COVID epidemic, many studies showed older adults had worse outcomes and increased rates of functional decline [10]. Patients suffer from chronic symptoms after Medicina 2024, 60, 537 2 of 12 COVID-19 infection, which can become debilitating and affect the daily routine [11]. And frailty was associated with an increased risk of developing post-acute sequelae of COVID infection [12].…”
Section: Introductionmentioning
confidence: 99%